THE EFFECT OF AUTHENTIC ASSESSMENT AND TEACHING VARIATION TOWARD FIQIH LEARNING OUTCOMES (An Experiment at Ponpes An Nida Al IslamyBekasi) - Eva Dwi Kumala Sari; Ihwan Mahmudi (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
This study aims to determine: (1) differences in fiqihlearning outcomes between students who are given an assessment of the performance and assessment of the essay. (2) to find out the interaction between authentic assessment and teaching variation on the results of fiqh learning. (3) differences in fiqh learning outcomes for students given a teaching style variation of teaching between students given an assessment of performance and assessment essays. (4) differences in fiqh learning outcomes for students given variations teaching instructional media between students given an assessment of performance and assessment essays. This research was conducted at An Nida Al Islamy Islamic Boarding School in Bekasi. With a sample size of 40 students using cluster random sampling techniques. Fiqh learning outcomes data are obtained through learning outcomes tests. The results showed that (1) jurisprudence learning outcomes of students who were given higher performance ratings than those given essay assessment, (2) there was an interaction effect between authentic assessment and teaching variation on fiqh learning outcomes, (3) for students with variations in teaching with style teaching, jurisprudence learning outcomes of students who are given a performance assessment, higher than the results of jurisprudence learning students who are given essay assessment, and (4) for students who are given a variety of teaching learning media, student jurisprudence learning outcomes that are given performance ratings, lower than learning student jurisprudence given essay assessment.